The culture of Thahârah in the Corona Virus Pendemic: An Offer to Prevent the Spread of Covid-19 with Islamic Jurisprudence Approach - Nurdin, Zurifah (Madania: Jurnal Kajian Keislaman, 2020)
Islamic teachings explain comprehensively how to purify, clean the body and the environment from uncleanness, and to use water and other washing media in a measured manner. In the concept of Islamic theory, this purification activity is known as thahârah. Due to the wide transmission of the Corona Virus Disease 2019 or Covid-19 throughout the world, this article offered preventive measures to restrain the spread of Covid-19 by practicing thahârah consistently based on a fiqh perspective. This study employed literary research method which traced a number of books by Islamic scholars related to the thahârah or purification procedures. After the data was collected, the analysis was carried out by analyzing, processing, and interpreting the data into a conclusion. The results revealed that in addition to eliminating hadats, dirt, and impurity, thahârah activities such as wudhu, tayamum, titual bathing, and teeth brushing benefit for physical and spiritual health. If thahârah is practiced consistently; as a cleaning up routine activity, it will diminish the spread of Covid 19. Instead of just washing hands, for instance, it is recommended to do wudhu even if it is not for praying. Viruses sticking to the hands and face will be washed away and disappear if a person performs wudhu properly according to the teachings of the Prophet Muhammad.  The research has shown that wudhu contains tremendous benefits for health as it can stimulate energy in the body and improve blood circulation. Ajaran Islam secara rinci menjelaskan bagaimana bersuci, membersihkan badan dan lingkungan dari najis, dan bagaimana menggunakan air dan media pencuci lainnya dengan terukur. Aktivitas bersuci tersebut dalam konsep Islam disebut thahârah. Sehubungan dengan telah menyebarnya virus Corona 2019 atau Covid-19  yang melanda ke seluruh dunia, artikel ini menawarkan upaya tindakan preventif pencegahan tertularnya Covid-19 dengan membudayakan thahârah  secara konsisten berdasarkan perspektif fikih. Penelitian ini menggunakan metode literary research, yakni menelusuri sejumlah buku-buku karya ulama Islam yang berhubungan dengan thahârah atau tatacara bersuci menurut fikih Islam. Setelah data terkumpul, dilakukan analisis dengan mengkalisifikasi, mengolah, dan menginterpretasi data menjadi suatu kesimpulan. Dari hasil analisis tersebut dapat disimpulkan bahwa selain bertujuan menghilangkan hadas, kotoran, dan najis, kegiatan thahârah seperti wudhu, tayamum, mandi, dan bersiwak bermanfaat untuk kesehatan jasmani dan rohani. Jika aktivitas thahârah ini dibudayakan secara konsisten, dalam arti dijadikan aktivitas yang rutin dalam membersihkan sesuatu, penyebaran Covid-19 akan tertekan menjadi minimal. Daripada mencuci tangan saja, misalnya, lebih baik sekalian berwudhu walaupun tidak untuk melakukan salat. Virus yang menempel di tangan dan wajah akan terbasuh dan lenyap jika seseorang melakukan wudhu dengan benar sesuai dengan ajaran Nabi Muhammad saw. Penelitian membuktikan bahwa wudhu mengandung manfaat yang besar bagi kesehatan karena mampu merangsang dan menstimulus energi dalam tubuh serta melancarkan peredaran darah.